2020
DOI: 10.18699/vj20.603
|View full text |Cite
|
Sign up to set email alerts
|

Erratum to: “Gas chromatography-mass spectrometry in the taxonomy of Miscanthus”

Abstract: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Genomic C-values are also attracting increasing attention from plant taxonomists, as they often help to delineate different taxa and have the potential to influence taxonomic decisions [ 38 ]. The best methods to study plant taxonomy are PCA and cluster analysis [ 39 , 40 ]. Cluster analysis showed that jujube germplasms in Linxian and other sub-regions were interrelated and independently clustered, indicating that their genetic base in Linxian is richer and the genetic background is more complex.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic C-values are also attracting increasing attention from plant taxonomists, as they often help to delineate different taxa and have the potential to influence taxonomic decisions [ 38 ]. The best methods to study plant taxonomy are PCA and cluster analysis [ 39 , 40 ]. Cluster analysis showed that jujube germplasms in Linxian and other sub-regions were interrelated and independently clustered, indicating that their genetic base in Linxian is richer and the genetic background is more complex.…”
Section: Discussionmentioning
confidence: 99%
“…Шумным получено 12 авторских свидетельств и патентов на сорта растений и технологии. Отдельное внимание посвящено получению сортов зерновых культур на основе отдаленной гибридизации (Abakumov et al, 2017;Arbuzova et al, 2009;Belan et al, 2012;Laikova et al, 2013), созданию генетических линий и доноров для получения сортов гороха с повышенной азотфиксацией (Nazaryuk et al, 2005;Sidorova et al, 2001;Sidorova, Shumny 1998;2003), сравнительным генетическим исследованиям сортов, созданных в разные периоды селекции (Khlestkina et al, 2004a,b), а также всестороннему изучению новой технической культуры -мискантусу (Gismatulina et al, 2014;Goryachkovskaya et al, 2016;Kapustyanchik et al, 2020;Shumny et al, 2010;Slynko et al, 2013;. В.К.…”
unclassified